RANCANG BANGUN TRAINABLE ROBOT ARM BERBASIS ARDUINO MEGA 2560 SEBAGAI MEDIA PRAKTIKUM DI LABORATORIUM TEKNIK ELEKTRO UNIVERSITAS PEMBANGUNAN PANCABUDI MEDAN - Hutapea, Marshal; Dalimunthe, Mhd Erpandi; Saragih, Yuliarman (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
The design of the Trainable Robot Arm is carried out as a learning medium in the lab. Electrical Engineering University of Development Pancabudi Medan. Trainable Robot Arm is a robotic arm designed to facilitate the process of robot applications in carrying out object transfer tasks without the need to do complex programming every time you want to change the robot's movements. The design of this arm robot is divided into 3 parts, the first is the design and manufacture of robot mechanics, the second is the design and manufacture of robot control/electricity and the third is the manufacture of robot software/programs. The mechanical design of the robot begins with making a 3D design of the robot frame utilizing the non-commercial version of the Fusion360 CAD software, then the 3D design is printed using a 3D Printing machine with PETG (Polyethylene Terephthalate) plastic material. The robot arm is designed to have a 5-DOF (Deegre of Freedom) system, namely Base, Shoulder, Elbow, Wrist and Gripper. As a drive, 5 servo motors with torque are used each, 25 kg/cm for Base and Shoulder, 11kg/cm for Elbow and Wrist, and 1.8 kg/cm for Gripper. From the test results, the Trainable robot arm successfully stores and repeats movements that have been trained to move objects with a mass of 100 grams at a position of 23cm from the axis of the robot arm to the x-axis to a position of 20cm from the axis of the robot to the y-axis as many as 8 repetitions without failure.